Primary Leiomyosarcoma of the Colon: A Report of Two Cases, Review of the Literature, and Association with Immunosuppression for IBD and Rheumatoid Arthritis - Jessica S. Crystal; Kristin Korderas; David Schwartzberg; Steven C. Tizio; Min Zheng; Glenn Parker (Case Reports in Surgery)
Primary leiomyosarcomas (LMS) of the colon are rare and aggressive neoplasms and have been infrequently reported in the literature. These tumors are more aggressive and have poorer prognoses than adenocarcinoma of the colon and are often mistaken as such on initial evaluation. While the former has a clear association with inflammatory bowel disease (IBD), this correlation is not known to exist with LMS and IBD. Nor is there a known link between LMS and the immunosuppression for IBD, despite the known association between malignancy and immunosuppression for other diseases. Due to the low prevalence of this disease entity, there is limited knowledge and literature on the approach to diagnosing and treating these neoplasms, especially in the setting of the aforementioned comorbidities. Here, we describe two cases of this rare entity, presenting in two different circumstances: one in the setting of immunosuppression for IBD and arthritis, with a synchronous urothelial carcinoma, and the second appearing as the source of an acute abdomen. Both diagnoses were established following pathologic analysis.